Predictors and Long-Term Outcome of Ablation of Discrete Pre-potentials in Patients With Idiopathic Ventricular Arrhythmias Originating From the Aortic Sinuses of Valsalva - Wei, Hui-Qiang; Guo, Xiao-Gang; Zhou, Gong-Bu; Sun, Qi; Yang, Jian-Du; Xie, Hai-Yang; Liang, Jackson; Zhang, Shu; Wu, Shulin; Ma, Jian (Frontiers in Cardiovascular Medicine, 2021)
Background The predictability and long-term outcome of the discrete prepotential (DPP) of idiopathic ventricular arrhythmias (VAs) arising from the aortic sinuses of Valsalva (ASV) have not been fully identified. Methods Of 687 consecutive patients undergoing ablation of outflow tract VAs, there were 105 (15.3%) patients with VAs originating from the ASV region who were included. Detailed mapping was performed within the ASV in all patients. Electrocardiographic, electrophysiological parameters and long-term success rate were compared between patients with and without the DPPs. Results A DPP was recorded in 67 of 105 (63.8%) patients, including 38 left sinus of Valsalva (LSV)-VAs (38/105, 36.2%) and 29 right sinus of Valsalva (RSV)-VAs (29/105, 27.6%). The patients with DPPs had wider QRS duration (152±17ms vs. 145±14ms, P<0.001). The average of earliest activation time was significantly earlier in patients with DPPs (-38.6±8.5ms vs. -27.7±5.7ms, P<0.001). Mean time from the first lesion to elimination of VAs was shorter in patients with DPPs (2.3±2.1s vs. 4.9±1.0s, P<0.001). A stepwise logistic multivariable analysis identified only younger age as a significant predictor of DPP (age ≤ 35.5 years predicted DPP with 92.9% positive predictive value). During a follow-up duration of 42.5±22.3 months, 63 (94.0%) patients with DPPs and 30 (78.9%) patients without DPPs remained free of recurrent VAs (P=0.027). Conclusion DPPs were observed in 63.8% of patients with VAs arising from the ASV. Ablation in patients with DPPs was associated with higher long-term success. DPPs were seen more commonly in younger (≤ 35.5 years) patients.